Društvena znanost i interpretacija društvenih pojava / Social Sciences and Interpration of Social Occurences - Lavić, Senadin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
Lead Article of Scientific Debate on the Social Processes in Bosnia and Herzegovina on its Path of EU Ascension, 22 April 2014.